Assessment of radiological hazards of soils from the city of Bitola (Macedonia) and its environs - Irena Zlatanovska, Trajče Stafilov, Robert Šajn, Bojana Dimovska Gonovska, Snežana Dimovska, Jovan Janusheski, Shaban Memetie, Lambe Barandovski (Taylor and Francis, 2024)
To establish the radioactivity level of soils and assess the associated radiological impact on residents, 58 samples from the town of Bitola and its environs were collected. After conducting gross alpha and gross beta measurements with a gas-flow proportional counter as a preliminary screening test, subsequent gamma-spectrometry measurements reveal the presence of 40K, 226Ra, 232Th, and 137Cs in the soil samples as radionuclides with the highest impact. The absorbed gamma dose rate, the annual effective dose, radium equivalent activity, external hazard index, gamma index, excess lifetime cancer risk, and annual gonadal dose were calculated using the obtained activity concentrations of the radionuclides. Upon comparison with similar studies conducted in the Balkan countries, the obtained results for radiation hazard indices were found to be the highest in the region. Coloured maps were generated to visually represent the spatial distribution of the absorbed gamma dose rate in air and annual effective dose, clearly indicating the combined influence of geology and human activities, including the nearby thermoelectric power plant operation.
Keywords: Radionuclides, Bitola, radiation hazard, gamma spectrometry, soil